Evaluation of cosmetic outcome and patient satisfaction following adhesive strips and staples wound closure in primary total knee arthroplasty - Essien UE; Obi CM; Inyang U; Ubaha A (Ibom Medical Journal)
Background: Most surgical wound closure techniques include using materials that may require removal after surgery. Surgical skin sutures and staples are popular skin closure materials that require removal after surgery and are usually associated with patient discomfort and crosshatching of the skin.